A Functional Metagenomic Analysis of Tetracycline Resistance in Cheese Bacteria - Flórez, Ana B.; Vázquez, Lucía; Mayo, Baltasar (Frontiers in Microbiology, 2017)
Metagenomic techniques have been successfully used to monitor antibiotic resistance genes in environmental, animal and human ecosystems. However, despite the claim that the food chain plays a key role in the spread of antibiotic resistance, metagenomic analysis has scarcely been used to investigate food systems. The present work reports a functional metagenomic analysis of the prevalence and evolution of tetracycline resistance determinants in a raw-milk, blue-veined cheese during manufacturing and ripening. For this, the same cheese batch was sampled and analyzed on days 3 and 60 of manufacture. Samples were diluted and grown in the presence of tetracycline on plate count milk agar (PCMA) (non-selective) and de Man Rogosa and Sharpe (MRS) agar (selective for lactic acid bacteria, LAB). DNA from the cultured bacteria was then isolated and used to construct four fosmid libraries, named after the medium and sampling time: PCMA-3D, PCMA-60D, MRS-3D, and MRS-60D. Clones in the libraries were subjected to restriction enzyme analysis, PCR amplification, and sequencing. Among the 300 fosmid clones analyzed, 268 different EcoRI restriction profiles were encountered. Sequence homology of their extremes clustered the clones into 47 groups. Representative clones of all groups were then screened for the presence of tetracycline resistance genes by PCR, targeting well-recognized genes coding for ribosomal protection proteins and efflux pumps. A single tetracycline resistance gene was detected in each of the clones, with four such resistance genes identified in total: tet(A), tet(L), tet(M), and tet(S). tet(A) was the only gene identified in the PCMA-3D library, and tet(L) the only one identified in the PCMA-60D and MRS-60D libraries. tet(M) and tet(S) were both detected in the MRS-3D library and in similar numbers. Six representative clones of the libraries were sequenced and analyzed. Long segments of all clones but one showed extensive homology to plasmids from Gram-positive and Gram-negative bacteria. tet(A) was found within a sequence showing strong similarity to plasmids pMAK2 and pO26-Vir from Salmonella enterica and Escherichia coli, respectively. All other genes were embedded in, or near to, sequences homologous to those of LAB species. These findings strongly suggest an evolution of tetracycline resistance gene types during cheese ripening, which might reflect the succession of the microbial populations. The location of the tetracycline resistance genes in plasmids, surrounded or directly flanked by open reading frames encoding transposases, invertases or mobilization proteins, suggests they might have a strong capacity for transference. Raw-milk cheeses should therefore be considered reservoirs of tetracycline resistance genes that might be horizontally transferred.